The Theme of “Hopelessness” Among the Diwan School Poets: The Example of Abbas al-Akkad - Rümeysa Zeynep Uylaş (Şarkiyat Mecmuası)
The formation of a new literary movement—as a result of the collapse of the Ottoman Empire and the nationalist movement that dominated the world—gave rise to many new tendencies and schools of thought. Poetry, the most important tool influencing the Arab masses appeared as nationalist and political poetry,as a reflection of modern society, and as anti-colonial poetry born of the French and British occupations. Especially after the 19th century, the literati and intellectuals in Egypt and Syria carefully followed the pioneered literary, political, and ideological movements. For example, there was the Neoclassical School formed by Baroudi (1839–1904), Ahmed Shawqy (1868–1932), and Hafez Ibrahim (1871–1932). It focused on the revival of Arabic poetry and considered ancient poetry as an inspiration for its structure and subjects. Subsequently, the poets of the Diwan School, consisting of Abbas al-Akkad (1889–1964), Ibrahim Abdel Rahman Shokry (1886–1958), and Abdal-Qadir al-Mazny (1890–1949), performed a series of innovations in Arabic poetry and literary criticism, and led the modern literary movements that followed, such as Mahjar and Apollo. This movement, which focuses on modern poetry in Arabic literature, includes a completely different perspective from ancient poetry. Specifically, the value of poetry is in the sincerity of the poet’s feelings (sidku’ş-şi’r). The theme of “hopelessness,” which came to the forefront because of the social and political dilemmas and uncertainties that dominated the period and the influence of Western Romantic poets, is clearly seen in their poems. Thus, we examine this particular theme by using the example of Abbas al-Akkad, the strongest representative of this school.